2014
DOI: 10.1002/anie.201404568
|View full text |Cite
|
Sign up to set email alerts
|

Membrane Deformation by Neolectins with Engineered Glycolipid Binding Sites

Abstract: Lectins are glycan-binding proteins that are involved in the recognition of glycoconjugates at the cell surface. When binding to glycolipids, multivalent lectins can affect their distribution and alter membrane shapes. Neolectins have now been designed with controlled number and position of binding sites to decipher the role of multivalency on avidity to a glycosylated surface and on membrane dynamics of glycolipids. A monomeric hexavalent neolectin has been first engineered from a trimeric hexavalent bacteria… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
56
0
1

Year Published

2015
2015
2021
2021

Publication Types

Select...
9
1

Relationship

6
4

Authors

Journals

citations
Cited by 56 publications
(59 citation statements)
references
References 19 publications
2
56
0
1
Order By: Relevance
“…For example, a hexavalent β -propeller neolectin was designed to bind glycolipids, and it was found that at least two binding sites are required for avidity. The distance between two adjacent binding sites strongly affects the ability of the protein to bend and invaginate membranes 11 . Although lectins are well-known for their medical properties, many are too toxic to be of clinical use.…”
Section: Introductionmentioning
confidence: 99%
“…For example, a hexavalent β -propeller neolectin was designed to bind glycolipids, and it was found that at least two binding sites are required for avidity. The distance between two adjacent binding sites strongly affects the ability of the protein to bend and invaginate membranes 11 . Although lectins are well-known for their medical properties, many are too toxic to be of clinical use.…”
Section: Introductionmentioning
confidence: 99%
“…Proteins such as Shiga and cholera toxin B subunits as well as capsid lectins from SV40 and norovirus with multivalent binding sites are capable of clustering glycosphingolipids, resulting in the formation of membrane invaginations (1)(2)(3)(4). The B subunit of Shiga toxin (STxB) produced by Shigaella dysenteriae can bind up to 15 molecules of the globoside Gb 3 , thereby driving curvature changes of cellular and artificial membranes (1,5).…”
mentioning
confidence: 99%
“…Reducing the valency from six to three by engineering one of the two binding sites per monomer resulted in a trimeric trivalent lectin that lost the capacity to induce membrane invaginations in GUVs [94]. A further step forward to control the number and the position of each of the binding sites in order to decipher the role of multivalency on membrane dynamics of glycolipids was the design of neolectins [95,96]. Starting from the trimeric hexavalent bacterial lectin RSL, a monomeric hexavalent neolectin was engineered with similar functional properties by introducing appropriate linkers.…”
Section: Neolectinsmentioning
confidence: 99%